2014
DOI: 10.1021/nn504898p
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Nanomaterial Bio-Interface by Addition of Mesoscale Secondary Features: Crinkling of Carbon Nanotube Films To Create Subcellular Ridges

Abstract: Biological cells often interact with their local environment through subcellular structures at a scale of tens to hundreds of nanometers. This study investigated whether topographic features fabricated at a similar scale would impact cellular functions by promoting the interaction between subcellular structures and nanomaterials. Crinkling of carbon nanotube films by solvent-induced swelling and shrinkage of substrate resulted in the formation of ridge features at the subcellular scale on both flat and three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…† These effects were attributed to the capillary forces generated by the drying process. 19,28 The electrodes that underwent such processes (UV-ozone treatment + aqueous solution) maintained their properties up to 40 days in an aqueous solution, as conrmed in previous work, 27 indicating that the modied electrodes were electrochemically stable and mechanically robust. Subsequent O 2 plasma treatment for 5 min, which was necessary for the PDL coating process, did not produce further deformations, as shown in Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…† These effects were attributed to the capillary forces generated by the drying process. 19,28 The electrodes that underwent such processes (UV-ozone treatment + aqueous solution) maintained their properties up to 40 days in an aqueous solution, as conrmed in previous work, 27 indicating that the modied electrodes were electrochemically stable and mechanically robust. Subsequent O 2 plasma treatment for 5 min, which was necessary for the PDL coating process, did not produce further deformations, as shown in Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Among these engineered electrodes, electrodes with modi-ed with non-planar nanostructures; pillars, 8 gold spines, 9 nanowires or nanotubes exhibited exceptionally good performance for extracellular recording electrode, due to their high surface areas and vertical geometry, which is crucial for electrode-cell coupling. [19][20][21][22] In that regard, vertically aligned carbon nanotubes (VACNTs) show promise as neural interfacing electrode, since carbon nanotubes show excellent electrical conductivity, chemical and mechanical stability, and protruded geometry that could be tightly wrapped around by cells to decrease the membrane-electrode distance and to increase seal resistance. The excellent performances of CNTs as neural electrode materials have been demonstrated in recordings of neural activity in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports show that CNTs are suitable for adsorbing certain proteins from culture media thus stimulating cell growth, supporting neuron attachment, growth, as well as differentiation and long-term survival [13][14][15][16]. CNTs have also been successfully used to mechanically reinforce hydrogels and create electrically conductive nanofibrous networks, enhancing bio-interface with the neural and cardiac cells [17][18][19][20]. Furthermore, such electrically conductive cues can also maintain and promote neuronal electrical activity in cultured cell networks, and mimic neural processes when organized into bundles [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…2(b) and 3(d)). Actually, it has been demonstrated that neurons sense and actively respond to nanoroughness with a sensitivity of a few nanometers [20]. Previous studies have shown evidences that the use of CNT films can enhance spontaneous electrophysiological activity of neurons and might affect neural maturity and network formation [21,29].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of CNTs in 1991, they have become one of the most promising materials for designing electrodes in electrochemical devices, owing to their large specific surface area, good mechanical properties, excellent stability, and high conductivity . Due to the relatively high cost of CNTs, they are usually not used in bulk but to modify other metal or carbon‐based anode materials . CNTs‐modified anodes usually show a well‐defined secondary nanostructure, i.e., nanofibrous feature and bimodal porosity, often yielding excellent biocompatibility.…”
Section: Carbon‐based Electrodes In Mfcsmentioning
confidence: 99%